2021
DOI: 10.20885/jkki.vol12.iss3.art11
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation and fortification program in eradicating micronutrient deficiencies in Indonesia

Abstract: Micronutrients play a significant role in metabolism reaction although this only needs a few micronutrients such as iron (Fe) and folic acid as folate substitutes. Fortification and supplementation program aims to meet the requirement of micronutrients by providing synthetic formula. The Indonesian government has applied iron-folic acid fortification (IFA) in flour. Moreover, the IFA supplementation program was given to vulnerable groups, pregnant mothers and women at reproductive age, including adolescent gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Utilizing the most recent data from the Indonesian Family Life Survey, and controlling for a full range of socioeconomic factors, it was revealed that mother's education, water and sanitation conditions, household poverty and access to health care strongly influence chronic malnutrition in children in Indonesia [17]. Nutrition education program, campaign for a healthy and balanced diet, fortification and protein consumption based local resources can be designated to assist the eradication of micronutrient deficiencies [18]. Fortified milk is an effective source of complementary nutrition to supplement children in need when consumed in the right amounts in addition to a normal diet.…”
Section: Figure 2 Documentation Community Service Activities At Sidod...mentioning
confidence: 99%
“…Utilizing the most recent data from the Indonesian Family Life Survey, and controlling for a full range of socioeconomic factors, it was revealed that mother's education, water and sanitation conditions, household poverty and access to health care strongly influence chronic malnutrition in children in Indonesia [17]. Nutrition education program, campaign for a healthy and balanced diet, fortification and protein consumption based local resources can be designated to assist the eradication of micronutrient deficiencies [18]. Fortified milk is an effective source of complementary nutrition to supplement children in need when consumed in the right amounts in addition to a normal diet.…”
Section: Figure 2 Documentation Community Service Activities At Sidod...mentioning
confidence: 99%